Zadanie 51 pls na jtr

Odpowiedź:
(x + 5)/(x - 3) = x/(x - 2)
założenie:
x - 3 ≠ 0 ∧ x - 2 ≠ 0
x ≠ 3 ∧ x ≠ 2
D: x ∈ R \ { 2 , 3 }
(x + 5)/(x - 3) = x/(x - 2)
(x - 2)(x +5) = x(x - 3)
x² - 2x + 5x - 10 = x² - 3x
x² + 3x - 10 =x² - 3x
x² - x² + 3x + 3x = 10
6x = 10
x = 10/6 = 1 4/6 = 1 2/3
Odpowiedź:
Szczegółowe wyjaśnienie:
(x + 5)/(x - 3) = x/(x - 2)
założenie:
x - 3 ≠ 0 ∧ x - 2 ≠ 0
x ≠ 3 ∧ x ≠ 2
D: x ∈ R \ { 2 , 3 }
(x + 5)/(x - 3) = x/(x - 2)
(x - 2)(x +5) = x(x - 3)
x² - 2x + 5x - 10 = x² - 3x
x² + 3x - 10 =x² - 3x
x² - x² + 3x + 3x = 10
6x = 10
x = 10/6 = 1 4/6 = 1 2/3